Manajemen Event Dalam Penguatan Branding Kota Wisata dan Budaya - Marta, Revi; Hafivi, Ilham; Diego, Diego; Trianto, Indra (Universitas Prof. Dr. Moestopo (Beragama), 2024)
Entertainment is a human need fulfilled through tourism, which not only provides enjoyment but also offers new experiences. The tourism sector has significant potential to boost local and national economies, requiring effective management and promotion through various strategies, including events. This research highlights the crucial role of event management in strengthening the branding of Sawahlunto City as a